Pidana dan Pemidanaan dalam Perundang-undangan Di Indonesia - Nurjanah, Siti (JURNAL ISTINBATH, 2011)
Crime is the protection to the society and to break the laws and the theory about crime. The target of crime is: prevention (general and special), protection of society, to keep the solidarity, and compensation / balance. So, crime have to be adapted to the condition of ideologiy, yuridis and sosiology where that theory will be applied. A politics of criminal is not only thought of by the scientists of law, but also involving the people and power that criminal law order.Key Word : Crime, ptotection of society, a politic of criminalÂ